Indonesian health care practitioner’s perception on gut-brain-axis and social-emotional concept - Ray Wagiu Basrowi; Tonny Sundjaya (World Nutrition Journal, 2022)
Background The microbiome-gut-brain-axis (GBA) concept has long been appreciated. It is recognized that the microbes resident in the gastrointestinal tract can influence brain physiology and the social-development competencies, and vice versa. Therefore, it is crucial for health care practitioners (HCPs) to understand this concept, especially in children; however, no study has been reported. Methods: This study used qualitative methods to explore HCPs’ perception and awareness about the microbiome-GBA concept. Data were collected through in-depth interviews using online video calls with HCPs, including general practitioners, pediatricians, and midwives. Results: We found that responders are aware of the microbiome-GBA concept, as this issue is often discussed in seminars and other events. They realized that gut health is a significant concern, and it is significantly impacting brain health and leads to social and emotional development (SED). This process starts from the early stages of life. Conclusion: The HCPs in our study have a good perception of the microbiome-GBA concept, e.g., a healthy brain is not possible without a healthy gut. As far as we are concerned, this is the first study to investigate the knowledge of HCPs about bidirectional communication of microbiome-GBA as an essential factor in child management.